PERÍODOS DE INTERFERÊNCIA DE PLANTAS DANINHAS, SELETIVIDADE DE MISTURAS EM TANQUE DE HERBICIDAS E TECNOLOGIA DE APLICAÇÃO NA CULTURA DO MILHO (Zea mays) - Helvig, Enelise Osco (2018)
An experiment was performed in a plastic greenhouse, climatized and with automatic irrigation system, aiming to evaluate the application dynamic deposition of glyphosate + atrazine + tembotrione (720 + 800 + 100,8 g i.a. or e.a. ha-1) tank mixture in six hybrids and two phenological stages of development. The experimental design was completely randomized with twelve treatments, represented by six hybrids, with and without application (RB9210™, DKB330 PRO2™, M30A37 PW™, P30F53YHR™, AS1555PRO2™, DKB285PRO2™) at two growth stages (3 and 5 leaves), with five repetitions. Two other experiments were carried out in the field at the farm school of Universidade Estadual do Centro-Oeste - UNICENTRO, Campus CEDETEG, Guarapuava-PR, during the 2016/2017 agricultural harvest, using the P2530™ and DKB 330PRO2™ hybrids. The second aimed to evaluate the spray deposition dynamic, as well as the selectivity and efficiency of herbicide tank mixtures combine or not with the foliar fertilizer Fertiactyl Pós™ in weed control in maize. The design was a completely randomized block design, with eight treatments and five repetitions, constituted by tank mixtures (g i.a. ha-1) + (mL pc ha-1): atrazina (ATR) + nicosulfuron (NIC) (1000 + 45); ATR + mesotrione (MES) (1000 + 144); ATR + tembotrione (TEM) (1000 + 100.8); ATR + NIC + Fertiactyl Pós™ (FEP) (1000 + 45) + (400); ATR + MES + FEP (1000 + 144) + (400); ATR + TEM + FEP (1000 + 100.8) + (400); and control with and without weeding. The second had the objective to determine the weeds coexistence periods (PAI) and control (PTPI) in the maize crop, in no-tillage and conventional systems, in high altitude. For this, four experiments were conducted in the field in Guarapuava-PR, during the 2016/2017 agricultural harvest, using the P2530™ (conventional) and P3271H™ (transgenic) hybrids in the no-tillage and conventional systems with crop residues of black oat (Avena strigosa). The experimental design completely randomized block design in a 2 x 7 factorial scheme with five repetitions, in the first factor was considered the periods of coexistence (PAI) and weed plant control (PTPI), and the second factor were the times of the weed community control, during: 0, 7, 14, 28, 42, 63 e 126 days after emergence (DAE). The application deposition in maize hybrids at V3 stage was superior comparing to V5 stage, with an increase of 37,1% on average. All maize hybrids presented higher phytotoxification in V3 stage compared to V5 stage. The FEP association with herbicides in tank mixtures did not interfere in the spray deposition in maize plants and Spermacoce latifolia, as well as in the weed control efficiency and grain yield, and could be used only to reduce phytotoxification and maintenance of chlorophyll levels of herbicide mixtures in maize crop. For P2530™ and P3271H™ hybrids, cultivated in conventional system with straw incorporation into the soil, the critical periods of weed interference (PCPI) were between 23 to 39 DAE and 23 to 35 DAE, respectively. At no-tillage on black oat straw, no PCPI was established, and only one single point control was needed between the periods of 21 to 33 DAE and 23 to 31 DAE for P2530™ and P3271H™ hybrids, respectively.